Typing operations manual and disposal of fixed assets: directions of improvement of accounting - I.M. Vygivska; S.E. Pyrizhok (Vìsnik Žitomirsʹkogo Deržavnogo Tehnologìčnogo Unìversitetu: Ekonomìčnì Nauki, 2016)
The lack of studies on the structure of business operations for the operation and disposal of fixed assets leads to undeveloped organizational and methodological provisions of the relevant accounting operations. In particular, the lack of comprehensive understanding of these operations can not account for the loss of alternatives and economic benefits from the use of fixed assets in various areas of economic activity. To streamline the organizational and methodological approaches to accounting of fixed assets, and monitor the effectiveness of the use and preservation of the property of the owner of the enterprise, and according to the analysis of literary sources showing a considerable amount of controversy in the existing approach of the authors, to characterize the operations manual and the disposal of fixed assets, the article suggests typing operations, exploitation and disposal of fixed assets. The main types of these operations include: 1) operation – storage, use, maintenance, repair and improvement; 2) disposal - sale, free transfer, exchange, cancellation due to moral and physical deterioration, capital contribution, financial lease, the installation of shortage, the transfer in payment of debt, the loss resulting from emergencies.